Opportunity Costs of Forest Conservation in Nepal - Rai, Rajesh K.; Nepal, Mani; Karky, Bhaskar S.; Timalsina, Niroj; Khadayat, Madan S.; Bhattarai, Nabin (Frontiers in Forests and Global Change, 2022)
Forest biomass may vary by species composition, location, management regimes, and management interventions. To assess the variation in biomass production by management regimes, we conducted a study in three physiographic regions (mid-hills, Siwaliks and Terai) of Nepal with four different management regimes (community forest, collaborative forest, protected area and protected forest). As community forest is the dominant forest management regime in Nepal, it was studied in all physiographic regions whereas the other regimes were selected only from the Terai. We interviewed a total of 1,115 forest user households, which was supplemented by high resolution satellite image analysis and forest inventory to estimate the costs and benefits of forest management and calculate the opportunity cost of conserving forest. Our estimates suggest that the opportunity cost of conserving forest in Nepal ranged from USD 654/ha in collaborative forest to USD 3,663/ha in protected forest in 2015. The associated opportunity cost of carbon sequestration was between USD 1.11 and USD 3.56 per tCO2. Of the forest management practices adopted, the silviculture-based intensive forest management practice had a far lower cost of forest conservation compared to the other forest management regimes. We found that such a practice is more beneficial to the forest dependent communities as it allows them to collect the non-timber forest products necessary for their daily needs.